Hyaluronic acid chloramide—Synthesis, chemical structure, stability and analysis of antimicrobials. (15th December 2020) - Buffa, Radovan; Hermannová, Martina; Sojka, Martin; Svozil, Vít; Šulc, Petr; Halamková, Pavlína; Pospíšilová, Michaela; Krejčí, Helena; Velebný, Vladimír
Highlights: Synthesis of highly chlorinated HA successfully performed. Detailed structural analysis by advanced 2D-NMR and LC/MS techniques. Product in its solid form showed acceptable 12-months stability. Basic antimicrobial and antiviral tests indicate a possible potential for applications in biomedicine. Abstract: Electron-deficient chlorine covalently immobilised on an amido group of hyaluronic acid (HA) can be potentially exceptional for applications requiring biodegradable and biocompatible polymers with enhanced antibacterial or antiviral activity. This expectation is supported by the assumption that a small amount of HA chloramide (HACl) is formed in the extracellular matrix under inflammatory conditions by a reaction of endogenous HA with hypochlorous acid (HClO) generated by a myeloperoxidase/H2 O2 /Cl − system. HACl synthesis optimisation showed significant limitations of HClO as an oxidative agent where only lower degrees of substitution (DS) was achieved. Commercially available oxidative agents based on chlorinated isocyanuric acid were successfully tested, producing the HA chain with almost entirely chlorinated amidic groups. The structure of the final HACl was thoroughly studied using advanced 2-dimensional NMR methodologies and LC/MS. Stability of HACl at different temperatures was monitored over 12 months. Preliminary antimicrobial and antiviral tests demonstrated the potential of HACl for applications in biomedicine.